2015
DOI: 10.1073/pnas.1424044112
|View full text |Cite
|
Sign up to set email alerts
|

Potential role for snoRNAs in PKR activation during metabolic stress

Abstract: Protein kinase RNA-activated (PKR) has long been known to be activated by viral double-stranded RNA (dsRNA) as part of the mammalian immune response. However, in mice PKR is also activated by metabolic stress in the absence of viral infection, and this requires a functional kinase domain, as well as a functional dsRNA-binding domain. The endogenous cellular RNA that potentially leads to PKR activation during metabolic stress is unknown. We investigated this question using mouse embryonic fibroblast cells expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
106
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 41 publications
6
106
1
Order By: Relevance
“…snoRNAs, which contain short duplexes interspersed with singlestranded regions, were recently reported to activate PKR. In some cases activation is dependent on a 5 ′ -ppp, whereas others are active in 5 ′ -OH and 5 ′ -p states (Youssef et al 2015), suggesting that the structural context can modulate the triphosphate dependence.…”
Section: Discussionmentioning
confidence: 99%
“…snoRNAs, which contain short duplexes interspersed with singlestranded regions, were recently reported to activate PKR. In some cases activation is dependent on a 5 ′ -ppp, whereas others are active in 5 ′ -OH and 5 ′ -p states (Youssef et al 2015), suggesting that the structural context can modulate the triphosphate dependence.…”
Section: Discussionmentioning
confidence: 99%
“…No reports exist in the literature to suggest that dsRNA is present under this stress condition, so we hypothesized an alternative method of PKR activation. Previous studies have elegantly shown the dependence of PKR activation by poly(I·C) in MEF cells genetically deficient in PKR and stably reconstituted with either wild-type human PKR (hPKR) or mutant human PKR (Mut hPKR) (56). We obtained cells in which residues lysine-64 in the dsRNA-binding motif (dsRBM) I and lysine-154 in the dsRNA-binding domain II were mutated to glutamines, impairing the binding of double-stranded RNA.…”
Section: Amplification Of Inos Has Proapoptotic Effects During Hyperomentioning
confidence: 99%
“…In mammals, multiple dsRBPs activate the inflammatory response upon interaction with dsRNA, including toll-like receptor 3 (TLR3), melanoma differentiation-associated protein 5 (MDA5), EIF2AK2 (also known as PKR), and DEXD/H-box helicase 58 (DDX58, also known as RIG-I) (de Faria et al 2013). These proteins were classically defined by their roles in initiation of an antiviral response, but recent data suggest that they are also activated by aberrantly regulated endogenous RNA (Hartner et al 2009;Pan et al 2011;Mannion et al 2014;Liddicoat et al 2015;Youssef et al 2015). Although the endogenous dsRNA pool is not well defined, host systems that regulate levels of dsRNA in the cell are known.…”
mentioning
confidence: 99%
“…Several other host receptors also bind specific endogenous dsRNA ligands under sterile conditions, including TLR3 and EIF2AK2, again emphasizing the importance of dsRNA in aberrant inflammation (Cavassani et al 2008;Green et al 2012;Youssef et al 2015). In these cases, a few endogenous ligands are known, including U2 RNA, snoRNAs, and tRNAs (Bernard et al 2012;Youssef et al 2015), but the complete pool of long dsRNA remains elusive.…”
mentioning
confidence: 99%